Communities, Performance and Practice Enacting Communities - Schaefer, Kerrie (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines how a predominantly negative view of community has presented a challenge to critical analysis of community performance practice. The concept of community as a form of class-based solidarity has been hollowed out by postmodernism's questioning of grand narratives and poststructuralism's celebration of difference. Alongside the critique of a notion of community has been a critical re-signification of community, following the thinking of philosopher Jean-Luc Nancy who conceives of community not as common being but as being-in-common. The concept of community as being-in-common generates questions that have been taken up by feminist geographers, J.K. Gibson-Graham, in theorising a post-capitalist approach to community-based development. These questions and approaches guide the analyses in researched case studies of community performance practice. The book revises theoretical debates that have defined the field of community theatre and performance. It asks how the critical re-signification of community aligns with these debates and, at the same time, opens new modes of critical analysis of community theatre and performance practice. Kerrie Schaefer has a PhD in Performance Studies from the University of Sydney, Australia. Before relocating to the UK in 2007, she was Lecturer in Drama at the University of Newcastle, NSW. She is currently an Associate Professor in Drama at the University of Exeter, UK. .
1. Preface - Enacting Community -- 2. Historical and theoretical perspectives on community-based theatre and performance practice -- 3. acta Community Theatre, the 'cycle of engagement' and a 'community of [community theatre] practice' -- 4. Yijala Yala - Creative Producing Cultural Livelihoods in the Pilbara -- 5. The Crossings (part of the Islands of Milwaukee): the agency of older bodies enacting pedestrian crossings -- 6. Articulating a community-engagement methodology in an authoritarian communitarian democracy - Drama Box's IgnorLAND Of Its Time performing the 'HDB nation' at Bukit Ho Swee. -- 7. Epilogue. .
Keywords: Performing arts; Theater; Cultural industries; Theater-History.; Site-specific theater; Theater-Production and direction; Theatre and Performance Arts; Theatre Industry; Contemporary Theatre and Performance; Applied Theatre; Site-Specific Performance; Theatre Direction and Production